Lipid oxidation and fatty acid profile related to broiler breast meat color abnormalities - Adriana Lourenço Soares (Brazilian Archives of Biology and Technology, 2009)
The aim of this work was to study the influence of lipid oxidation on broiler breast meat (Pectoralis major m) color abnormalities. There were 27.0 % more lipid oxidation in PSE in relation to normal meat and 41.0 % more in relation to DFD-like meat (p<0.05). The fatty acid profile was also significantly different since the arachidonic acid (AA) fraction increased 38.6 and 70.5 % in PSE meat comparing to normal and DFD-like meats, respectively. The ratio PUFA/SFA changed in these three types of meat: 0.736, 0.713 and 0.694 for PSE, normal and DFD-like meat respectively, reflecting the highest production of polyunsaturated fatty acids in the PSE meat samples. Results indicated that phospholipase A2 enzyme activities played a relevant role towards the development of PSE-meat syndrome in a cascade of biochemical reactions promoting the formation of free radicals from AA, which ultimately damaged the muscle membrane systems. A influência da oxidação lipídica no surgimento das anormalidades das cores do filé do peito de frango (Pectoralis major) foi avaliado. A oxidação lipídica foi 27 % maior em carnes PSE em relação ao normal e 41,0% em relação ao análogo DFD (p< 0.05). O perfil dos ácidos graxos foi também significantemente diferente desde que a fração do ácido araquidônico (AA) aumentou 38,6% e 70,5% em carnes PSE em comparação às carnes normais e análogas ao DFD, respectivamente. A razão PUFA/SFA se alterou nos três tipos de carne, 0,736, 0,713 e 0,694 para carnes PSE, normal e análogo ao DFD, respectivamente, refletindo a maior produção dos ácidos graxos polinsaturados em amostras PSE. Esses resultados corroboram os nossos anteriores, indicando que a atividade da enzima fosfolipase A2 tem um papel relevante no desenvolvimento da síndrome do PSE em uma cascata de reações bioquímicas promovendo a formação dos compostos radicais livres do AA que finalmente compromete os sistemas das membranas celulares do músculo.